Mechanism of Overburden Dumping by Applying SNI 7280:2022 - Fanteri Aji Dharma Suparno; Agus Prastyo; Siti Aminah (Geological Engineering Department Universitas Gadjah Mada, 2025)
The management of overburden containing Potentially Acid Forming (PAF) and NonAcid Forming (NAF) materials is essential to prevent the formation of acid mine drainage (AMD). This study aims to analyze the distribution of PAF and NAF materials based on lithological characteristics and design an overburden dumping mechanism based on SNI 7280:2022. Data were obtained from 90 borehole points in the PT X area, East Kutai. Lithology was dominated by sandstone and mudstone (PAF). The total overburden volume was 185,493,800 bcm, with 66.67% PAF and 33.33% NAF. The dump design used an encapsulation approach (1-3-7 NAF-PAF-NAF block configuration) to isolate PAF from air and water exposure. The calculated Factor of Safety (FK) using theBishop method was 1.545, indicating a stable slope.